New Direction to the Sustainable Development Goals in Job Creation Bill in Indonesia - Lumbanraja, Anggita Doramia (International Journal of Criminology and Sociology, 2021)
United Nations Sustainable Development Goals (UN SDGs) deliver a long list for UN Member countries to do, especially in the legal and regulatory frameworks. UN SDGs contain many kinds of human needs aspect, and it is not easy to regulate all through the conventional legislative process. It raises the needs of the omnibus bill use. This article studied the opportunities and the urgency of the omnibus bill use to solve this problem. The author uses a doctrinal method with literature studies to examine how SDGs can be obtained with the use of the omnibus bill. The omnibus bill has the potential to help countries achieve the UN SDGs. In the implementation stage, the author found that it is a normal phenomenon that a political will contains economic interests in the adaptation process, likewise, with the omnibus bill case in several countries. However, it does not erase the fact that there has been a wave of resistance in its implementation due to people's unpreparedness in accepting changes brought by the political policies that are contained in the controversial omnibus bill. Therefore, the government must ensure that the omnibus bill is open to the change opportunities demanded by the people to improve the omnibus bill.